Association of EPHB1 rs11918092 and EFNB2 rs9520087 with psychopathological symptoms of schizophrenia in Chinese Zhuang and Han populations. (29th March 2016) - Su, Li; Ling, Weijun; Jiang, Juan; Hu, Jing; Fan, Jingyuan; Guo, Xiaojing; Huang, Guifeng; Xie, Xinfeng; Long, Jianxiong
Abstract: Two single‐nucleotide polymorphisms (SNPs) (rs11918092 and rs9520087) were genotyped in Chinese Zhuang and Han populations. Symptoms of schizophrenic patients were assessed by the Positive and Negative Syndrome Scale. No association of any SNP with schizophrenic susceptibility was found. However, associations of rs9520087 with the total scale score ( P = 0.014), positive scale score ( P = 0.013), negative scale score ( P = 0.032), and general psychopathology scale score ( P = 0.031) were found in Zhuang patients. Additionally, rs11918092 was associated with positive scale score ( P = 0.035) in Han patients. The two SNPs might influence symptoms of schizophrenia.